(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Intraarticular calcaneal fractures are important because of their impact on ankle function and daily activities; therefore, surgery is usually performed. The fracture site can be reduced using the Essex-Lopresti method and then stabilized with various fixation devices. This study aimed to evaluate the treatment of calcaneal fractures using Essex-Lopresti closed reduction and cancellous screw fixation. Method: This was a descriptive prospective study. 33 patients (38 calcaneal fractures) who underwent this procedure participated in this study. The Bohler angles and Gissane angles were measured before and after the surgery. Functional scores, bone healing, and complications were also assessed. Results: All the patients returned to normal Bohler angles and Gissane angles after surgery. Ankle function, as assessed by the AOFAS and MFS, was rated as good to excellent in most cases, with scores exceeding 80 points on both scales. Conclusions: Essex-Lopresti closed reduction and cancellous screw fixation are safe and effective treatment methods for intra-articular calcaneal fractures.